Does Purchase Decision Still Relevant To Mediate Customer Satisfaction For Aqua Bottled Water Products? - Abdullah, M Said; Barung, Rachmat; Naska N, Naska N; Syahril, Syahril; Ramli S (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study wants to test whether the marketing mix, consumer behaviour and brand image are still relevant to be used as a marketing medium for mineral water products in the Aqua market to provide consumer satisfaction in making purchases amid the existence of competing products that interfere with the market share of Aqua products in West Sulawesi. The sample used 270 with porposive sampling technique with the covariance based structural equation model (CB-SEM) research method analysing respondent response data. Research findings marketing mix, consumer behavior has a significant effect on purchasing decisions, brand image has an insignificant effect on purchasing decisions, marketing mix has an insignificant effect on customer satisfaction, consumer behavior, brand image has a significant effect on customer satisfaction, marketing mix, consumer behavior mediated buying decision has a significant effect on customer satisfaction, brand image mediated buying decision has an insignificant effect on customer satisfaction